Crise de hegemonia e emergência de novos atores na Bolívia: o governo de Evo Morales - Ayerbe, Luis Fernando [UNESP] (CEDEC, 2011)
The presidency of Evo Morales, indigenous leader and who heads the party Movement Towards Socialism (MAS), opens a series of transformations in several dimensions. The changes in socio-economic and political power express the critic of long-term coloniality relations between a dominant white elite and an indigenous subordinate majority that deepens after national independence. Following this perspective, present in sectors of support to the government, the strategy of the MAS cannot follow the tradition of social revolutions that operated structural breaks in the mode of production and the state organization, but points to a new decolonizing revolution, cultural and political, articulating an indigenism of broad nature, flexible and open to popular social movements. This view is facing critics in sectors of the left that identify the renewal of capitalist modernization process initiated in 1952 under the leadership of the Nationalist Revolutionary Movement (MNR), extending citizenship and democratizing access to the state for recognition of Indians as such. From this perspective, the transformations proposed by MAS tend to favor a system restoration by diversifying its economic and social base. From the contrast provided by these two lines of interpretation, we intend to analyze the structural possibilities of the strategy of the government of Evo Morales, taking as historical reference the transformations wrought by the nationalist revolution of 1952 and the neoliberal reforms initiated in 1980.

A presidência de Evo Morales, liderança indígena e dirigente do partido Movimiento al Socialismo (MAS), abre um processo de transformações em diversas dimensões, em que as mudanças socioeconômicas e no poder político expressam uma perspectiva de longa duração que questiona relações de colonialidade entre uma elite dominante branca e uma maioria indígena subalterna, que se aprofundam após a independência nacional. Acompanhando essa perspectiva, predominante nos setores de apoio ao governo, a estratégia de poder do MAS não segue a tradição das revoluções sociais que operaram rupturas estruturais no modo de produção e na organização estatal bolivianas, mas aponta para uma nova revolução descolonizadora, política e cultural, que articula um indigenismo de natureza ampla, flexível e aberto aos movimentos sociais do campo popular. Essa concepção enfrenta críticas em setores da esquerda, que vislumbram uma renovação do processo de modernização capitalista iniciado em 1952, sob a liderança do Movimiento Nacionalista Revolucionario (MNR), ampliando a cidadania e democratizando o acesso ao Estado pelo reconhecimento dos indígenas como tais. Nessa perspectiva, a transformação proposta pelo MAS tenderia a favorecer uma recomposição do sistema diversificando sua base socioeconômica. A partir do contraste estabelecido por essas duas linhas de interpretação, pretendemos analisar as possibilidades estruturais da estratégia do governo de Evo Morales, tomando como referentes históricos as transformações operadas pela revolução nacionalista de 1952 e pelas reformas neoliberais iniciadas nos anos 1980.
Hegemonic crisis and emergence of new actors in bolivia: the government of evo morales
Keywords: Evo Morales; coloniality; nationalism; socialism; Evo Morales; colonialidade; nacionalismo; socialismo